Analisis Buku Tematik Siswa Muatan IPA Ditinjau dari Literasi Sains Unsur Pengetahuan dan Konteks (Studi Deskriptif Materi IPA Tema 9 Kelas VI Sekolah Dasar) - irma nur safitri; Endang Widi Winarni; Dwi Anggraini (JURIDIKDAS, 2022)
This study aims to describe the presentation of scientific literacy on the elements of knowledge and context in the Thematic book (9th theme : Menjelajah Angkasa Luar) for 6th grade elementary students. This type of research is qualitative using descriptive methods. This type of research is qualitative using descriptive methods. The subject of this research is the Thematic book (9th theme : Menjelajah Angkasa Luar) for 6th grade elementary students. The data collection techniques in this study were expert review sheets, documentation sheets and the results of the analysis of the Thematic book (9th theme : Menjelajah Angkasa Luar) for 6th grade elementary students. The data analysis technique in this research is qualitative data analysis. The results of the analysis show that the percentage of occurrences of the knowledge element indicator is 37.8%. The percentage of occurrences in the context element indicator is 40.73%. It can be ascertained that the emergence of scientific literacy indicators in basic knowledge is still low in the context element in the Thematic book (9th theme : Menjelajah Angkasa Luar) for 6th grade elementary students.Keywords: Scientific Literacy, Knowledge, Context, Thematic Books